1994
DOI: 10.1111/j.1600-0773.1994.tb00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Studies on One‐Year Treatment of Non‐Diabetic and Streptozotocin‐Diabetic Rats with Vanadyl Sulphate

Abstract: Streptozotocin-diabetic and non-diabetic rats were given vanadyl sulphate in drinking water at concentrations of 0.5-1.5 mg/ml for one year. It was found that vanadyl treatment did not produce persistent changes in plasma aspartate aminotransferase, alanine aminotransferase, and urea, specific morphological abnormalities in the brain, thymus, heart, lung, liver, spleen, pancreas, kidney, adrenal, or testis, or abnormal organ weight/body weight ratio for these organs in either non-diabetic or diabetic animals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 21 publications
5
20
1
1
Order By: Relevance
“…At time of death, vanadium levels (nmol/ml or nmol/g) in DT animals were: plasma, 7.8Ϯ1.0; liver, 30.6Ϯ3.7; muscle, 4.5Ϯ0.2; pancreas, 8.0Ϯ1.0; bone, 415.0Ϯ40.4; kidney, 129.4Ϯ6.9. These levels are similar to previously reported values in diabetic rats after one year of vanadium treatment (18). Vanadium levels were not statistically different between the DT-HC and DT-LC subgroups at 5 weeks.…”
Section: Variable Response To Vanadium Treatmentsupporting
confidence: 81%
“…At time of death, vanadium levels (nmol/ml or nmol/g) in DT animals were: plasma, 7.8Ϯ1.0; liver, 30.6Ϯ3.7; muscle, 4.5Ϯ0.2; pancreas, 8.0Ϯ1.0; bone, 415.0Ϯ40.4; kidney, 129.4Ϯ6.9. These levels are similar to previously reported values in diabetic rats after one year of vanadium treatment (18). Vanadium levels were not statistically different between the DT-HC and DT-LC subgroups at 5 weeks.…”
Section: Variable Response To Vanadium Treatmentsupporting
confidence: 81%
“…Corroborating our results, Dai et al [44] assessed the toxic effects of 0.5-1.5 mg/mL VOSO 4 in the drinking water of diabetic and healthy rats for a period of one year and observed no persistent changes in plasma AST or ALT.…”
Section: Resultssupporting
confidence: 61%
“…Assays of serum enzyme activities that are used as hepato-biliary function markers (ALT, ALP) were carried out, in view of the finding by Dai et al that vanadyl sulfate accumulates in the liver [44]. The results of these toxicity tests indicated (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They effectively control the diabetic state and prevent the development of complications in both insulin-dependent and noninsulin-dependent diabetes mellitus in experimental animals [6]. Clinical studies in type 1 diabetes patients showed that the daily insulin requirement decreased significantly [7].…”
Section: Introductionmentioning
confidence: 99%